Interferensi Fonologis Bahasa Indonesia Oleh Penutur Asli Bahasa Duri Di Desa Curio, Kecamatan Curio, Kabupaten Enrekang - Sartika S; Johar Amir; Azis Azis (Indonesian Journal of Social and Educational Studies, 2022)
Phonological Interference of Indonesian by Native Speakers of Duri Language in Curio Village, Enrekang Districts.This study aims to describe (1) the form of Indonesian phonological interference by native speakers of the Duri language in Curio Village, Enrekang Districts experiencing additional phonemes, (2) a form of Indonesian phonological interference by native speakers of the Duri language in Curio Village, Enrekang Districts which has reduced phonemes, and (3) a form of Indonesian phonological interference by native speakers of the Duri language in Curio Village, Enrekang Districts which undergoes a phoneme change.This research is a qualitative descriptive study. The data in this study are Indonesian utterances that experience phonological interference in the form of adding phonemes, reducing phonemes, and changing phonemes. The source of data in this study is the Curio village community who are native speakers of the Duri language. The data collection technique used is the listening technique, the conversational engagement listening technique, the recording technique, and the note-taking technique. The data obtained were analyzed through several stages, namely (1) data reduction, (2) data presentation, and (3) drawing conclusions.The results of data analysis show that the phonological interference of the Indonesian language by native speakers of the Duri language in Curio Village, Enrekang Districts is in the form of interference of adding phonemes that occurs in the middle of a word and the end of a word, interference of reducing phonemes that occurs at the beginning of a word, in the middle of a word, and at the end of a word, while interference with phoneme changes occurs at the beginning of a word, in the middle of a word, and at the end of a word.Keywords: Interference, Fhonological, Duri Language